Rapid and Sensitive Qualitative Duoplex Real-Time PCR Method for Discriminatory and Confirmatory Diagnosis of HTLV-1 and HTLV-2 Infections: Brazilian Multicentric Study - Rocha-Junior, Mauricio Cristiano; Rodrigues, Evandra Strazza; Slavov, Svetoslav Nanev; Assone, Tatiane; Pedreschi, Maíra; de La Roque, Debora Glenda Lima; Sousa, Maisa; Olavarria, Viviana; Galvão-Castro, Bernardo; Fonseca, Benedito Antonio Lopes da; Penalva de Oliveira, Augusto César; Smid, Jerusa; et al. (Frontiers in Medicine, 2022)
Human T cell lymphotropic virus (HTLV) is the caustive agent of two main conditions i.e. the HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and the adult T-cell leukemia/lymphoma (ATLL). HTLV diagnosis is based on serological and molecular approaches; however, an accurate and validated method is still needed. The objective of this study was to establish a rapid and sensitive molecular test to confirm and discriminate HTLV 1/2 types. The test validation was performed as a multicentric study involving HTLV confirmation centers throughout Brazil. Proviral DNA was extracted from whole blood and the amplification was performed using in-house designed primer and probe sets targeting the pol genomic region. An internal control to validate the extraction and amplification was also included. The limit of detection (LoD) of the assay was 3.9 copies/reaction for HTLV-1 and 10.9 copies/reaction for HTLV-2. The diagnostic sensitivity of the platform was 94.6% for HTLV-1, 78.6% for HTLV-2, and the specificity was 100% for both viruses. Cross-reactions of the test with human viruses including HAV, HBV, HCV, HIV-1/2, and parvovirus B19 were not observed. During the multicentric validation, the test was used to screen a total of 692 blood samples obtained from previously confirmed HTLV-positive individuals. From these, 91.1% tested positive being concordant with the previously obtained results. In conclusion, our duoplex-RT-PCR-HTLV1/2 presented adequate efficiency for HTLV-1/2 differentiation showing high sensitivity and specificity. Therefore, it can be a suitable tool for confirmation of suspected and inconclusive HTLV cases, prenatal and pre-transplant diagnosis, in Brazil and in other countries HTLV-endemic countries.